PESANTREN DAN WACANA FIKIH KONTEMPORER - Ansori Ansori; Agus Sunaryo; Munawir Munawir (Jurnal Penelitian Agama, 2011)
The concept of figh should be able to accommodate the interests of Muslims in Indonesia. For that reason, figh that should be formulated is one with local values and based on syari in guarding the five basic principles of determining law. The five principles are: keeping the faith, keeping the spirit, keeping the offspring, guarding property, and maintaining common sense. Figh should also be able to meet all the basic needs of the Muslims: primary (darunyyat), secondary (hajiyyat). and tertiary (luxunes) needs.